Application of three different methods for determination of optimum insulation thickness in external walls - Ucar, Aynur; Inalli, Mustafa; Balo, Figen (Wiley, 2011)
In this study, three different methods for determining the optimum thickness of used insulation material in external walls of building are presented. The first method is life cycle cost based on the energetic costs. The second method is thermoeconomic optimization based on the cost of insulation materials and fuel. Finally, the third method is optimization of insulation thickness by Turkish Thermal Insulation Standard-TS 825 based on heat energy requirement of buildings. The results show that the optimum insulation thicknesses vary between 3.2 and 12 cm, energy savings vary between 2.63 $/m2 and 4.35 $/m2, and payback periods vary between 1.7 and 2.7 yrs depending on the city and optimization method. (c) 2011 American Institute of Chemical Engineers Environ Prog, 2011
Keywords: insulation thickness; optimization; thermoeconomic